Pulmonary & Critical Care Medicine: Chronic Obstructive Pulmonary Diseases - Jindal Surinder K, Vijayan Vannan K; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2013)
This is the series of World Clinics Pulmonary and Critical Care Medicine: Chronic Obstructive Pulmonary Diseases. It is comprehensive and updated text as per the present day advances in the subject of Pulmonary and Critical Care. This periodical encompasses the latest guidelines for healthcare professionals for the care of chronic obstructive pulmonary diseases patients. The topics for this issue are selected keeping in mind the scientific needs of both basic scientists and clinicians. The contributors of each article are experts in their chosen field with several years of experience. The important basic science articles described in this issue include epidemiology, genetics, pathogenesis, and pathophysiology, including biomarkers and dyspnea in COPD. Acute exacerbations, comorbidities, and vascular dysfunctions are frequently encountered by physicians while treating COPD patients and recent advances on these aspects are described in 3 articles. Five chapters deal exclusively with management aspects of COPD. The important clinical issues described are imaging studies, treatment (both pharmacological and nonpharmacological), psychological/cognitive dysfunction, pulmonary rehabilitation, and oxygen therapy. Pulmonary rehabilitation is an area that requires more attention from physicians to improve the quality of life of these unfortunate patients.
Keywords: Pulmonary and Critical Care Medicine; Electronic books